Systematic Literature Review: Self-Harm in Indonesia and Its Influencing Factors - Rany Agustin Wulandari (KHD Production, 2025)
Adolescence is a transitional period that experiences a variety of significant changes. The existence of various pressures and challenges can cause adolescents to experience negative feelings which ultimately choose to engage in self harm behavior. There are several factors that cause self harm behavior. The purpose of this study is to gain an in-depth understanding of the behavior and forms of self harm and the factors that cause self harm. The study was conducted using Systematic Literature Review (SLR) through the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-analysis). The keywords used are self harm behavior, factors causing self harm, obtained 10 journal articles that match the inclusion criteria. Self harm behavior is done as an emotional response that cannot be expressed. It can take the form of self-mutilation, scratching, head banging, cutting, burning, drug abuse, tattooing and piercing, and even self-poisoning. Factors that cause self-harm behavior can be divided into two types, namely internal factors (Loneliness, Feelings of anxiety, Anger and guilt, Stress and depression, Communication problems, Low self-esteem, No self-confidence, Bipolar disorder and psychosocial problems, Parenting, Hatred, Gender, Skin color, Personality, Trauma, Loss, Genetics, Feeling like a failure, Parental neglect, Putting others first, Sadness), and external factors (Bullying, Social failure, Social and economic status, Sexual abuse victim, Internet, media, and cell phone use, Rejection from peers). Self harm behavior needs immediate prevention and management because if it is not treated immediately it will lead to suicide. There are 26 factors that cause self harm behavior.